2022
DOI: 10.1186/s13045-022-01360-x
|View full text |Cite
|
Sign up to set email alerts
|

The synthetic lethality of targeting cell cycle checkpoints and PARPs in cancer treatment

Abstract: Continuous cell division is a hallmark of cancer, and the underlying mechanism is tumor genomics instability. Cell cycle checkpoints are critical for enabling an orderly cell cycle and maintaining genome stability during cell division. Based on their distinct functions in cell cycle control, cell cycle checkpoints are classified into two groups: DNA damage checkpoints and DNA replication stress checkpoints. The DNA damage checkpoints (ATM-CHK2-p53) primarily monitor genetic errors and arrest cell cycle progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 196 publications
(285 reference statements)
0
13
0
Order By: Relevance
“…Several previous studies have confirmed that the cell cycle is a crucial factor affecting tumor growth ( 20 , 21 ). Our results showed that chaetoglobosin E induced G2/M phase arrest of KYSE-30 cells, followed by the down-regulation of cyclinB1, CDC2, and p-CDC2, and the up-regulation of p21.…”
Section: Discussionmentioning
confidence: 82%
“…Several previous studies have confirmed that the cell cycle is a crucial factor affecting tumor growth ( 20 , 21 ). Our results showed that chaetoglobosin E induced G2/M phase arrest of KYSE-30 cells, followed by the down-regulation of cyclinB1, CDC2, and p-CDC2, and the up-regulation of p21.…”
Section: Discussionmentioning
confidence: 82%
“…Smc4, a core subunit of condensing, has been reported to be associated with a variety of tumors, such as hepatocellular carcinoma ( 47 ), prostate cancer ( 48 ), and lung adenocarcinoma ( 49 ), and activated TGFβ/Smad signaling has been reported to promote the aggressive phenotype of glioma ( 50 ). Targeting poly (ADP-ribose) polymerase and cell cycle checkpoints, ATM-CHK2-TP53 and ATR-CHK1-WEE1, can benefit tumor therapy through a synthetic lethality mechanism ( 51 ). Moreover, WEE1 inhibition can boost anti-tumor immunity by activating ERV and the dsRNA pathway and strengthen sensitivity to immune checkpoint blockade ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…PARP inhibitors induce synthetic lethality in cancer cells with defects in DNA repair, particularly those with BRCA mutations. This is achieved by inhibiting an alternative repair mechanism, which leads to the accumulation of unrepaired DNA damage and subsequent cell death 33,34 . Recent studies have highlighted the signi cant effects of PARP inhibitors (PARPi) on shaping the tumor microenvironment, which leads to an enhanced antitumor immune response.…”
Section: Discussionmentioning
confidence: 99%